LINGUISTIC LANDSCAPE ON CAMPUS IN PONOROGO (A CASE STUDY OF SIGNS IN PONOROGO UNIVERSITIES) - Nefy Nosiani; Siti Asiyah; Diyah Atiek Mustikawati (Universitas Muhammadiyah Ponorogo, 2019)
This research aims to: (1) describe the types of linguistic landscape are used in Universities Ponorogo, (2) know purposes of the signs posted in Ponorogo Universities, (3) know the factors that Ponorogo Universities used that sign. This research design was qualitative research of case study. The researcher used observation and interview as the data collection technique. There are eight universities in Ponorogo, those are Universitas Darussalam Gontor, Universitas Merdeka, Institut Agama Islam Negeri Ponorogo, Unmuh Ponorogo, Akper Ponorogo, Insuri Ponorogo, and Akafarma Ponorogo, however, and only three universities gave permission for the researcher to conduct this research. The findings of observations, six of the eight campuses in Ponorogo have tried to display a sign that has finally become a special feature of the campus. This research concludes most of them still use the Indonesian language. While, campus managed to convey the purpose of the sign installation to the viewer. In other word, the sign viewer understands the purpose of each sign that is installed by giving opinions and implementing them in daily life.